Morfo-anatomia e desenvolvimento pós-seminal de cinco espécies de Bromeliaceae - Viana, Fábio Alessandro Padilha [UNESP] (2007)
The objective of the work was to describe and to compare the anatomy and the morphology of the seed and of the seedlings, as well as to describe the stages of the germination process of the seeds of tive bromeliads species. Comparing the results, the species of the gender Nidularium present form from fusiform to elliptic seed while the species Alcantarea imperialis and Pitcairnia flammea present prolonged formo The tegument of the studied seeds has coloration varying frem dark brown to black. The pattem of the cells is differentiated, therefore in Alcantarea imperialis the pattem is irregular, with the presence of wax granules, that is not noticed in the other species. In Pitcairnia fIammea the pattem is irregular occurring some difference in the form between the cells of the extremities and the cells of the medium area. Within relationship to the characterization of the germination, the species of Nidularium and the species Alcantarea imperialis present hipogeal germination while the species Pitcairnia fIammea presents epígeal germination. It was observed that the seeds of the species of Nidularium and of the species Pitcairnia fIammea are have one tegument, with basal embryo and rudimentare and they could be conical or prolonged. The abundant endosperm is constituted by small cells containing grains of starch. The plumule of the species of Nidularium has triangular and tiny form while in the species Alcantarea imperialis the plumule is piriformy and in the species Pitcairnia fIammea it is prolonged. The cells of the adaxial face of the leaves of Nidularium present prolonged pattem; in Alcantarea imperialis they are poliedrical and reticulate in Pitcaimia fIammea they are poliedrical and isodiametrical. The cells of the abaxial face of the leaves of the tive species are already poliedrical and reticulate...(Complete abstract, click electronic access below)